The Keynesian theory of economic development - Kurihara, Kenneth K. (London : George Allen & Unwin, 1959)
This book examines technical possibilities and limitations of economic growth in general and of the economic development of underdeveloped countries in particular. It provides comparative analyses of diverse growth problems of underdeveloped and developed economies throughout this volume. It also attempts to explain the operationally significant mechanisms of economic development in given socio-cultural conditions. Separate chapters, have been arranged so as to constitute an integrated theoretical whole and to facilitate an overall scheme of industrialization programming in less developed countries.
Includes bibliographical references and index.
lje 07/05/2018
Loans
Keywords: Economic development; Developing countries